The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/jms.4777
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace compounds and artifacts in nitrogen background measurements by proton transfer reaction time‐of‐flight mass spectrometry under dry and humid conditions

Abstract: A qualitative analysis was applied for the determination of trace compounds at the parts per trillion in volume (ppt v ) level in the mass spectra of nitrogen of different qualities (5.0 and 6.0) under dry and humid conditions. This qualitative analysis enabled the classification and discovery of hundreds of new ions (e.g., [S x ]H + species) and artifacts such as parasitic ions and memory effects and their differentiation from real gas impurities. With this analysis, the humidity dependency of all kind of ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 119 publications
(267 reference statements)
0
4
0
Order By: Relevance
“…Especially for small molecules, such artefacts can relate to either isobaric interferences, or the actual formation of the target compounds within the instrument upon fragmentation of larger compounds (Michoud et al, 2018;Salazar Gómez et al, 2021).…”
Section: 32)mentioning
confidence: 99%
“…Especially for small molecules, such artefacts can relate to either isobaric interferences, or the actual formation of the target compounds within the instrument upon fragmentation of larger compounds (Michoud et al, 2018;Salazar Gómez et al, 2021).…”
Section: 32)mentioning
confidence: 99%
“…Other suspected silanes and siloxanes that were quantified here by PTR-TOFMS were not observed in the two mask studies, yet other PTR-MS measurements on TMS have reported that this compound converts to dimethylsilandiol (DMSD; m/z 93.035) in the presence of water vapour, which supports the present observations. A signal detected at m/z 75.034 is likely associated with the loss of a methyl group from TMS, and two dominant signals observed at m/z 147.086 and m/z 149.048 could be attributable to the dehydration of pentamethyldisiloxane and tetramethylcyclodisiloxane, detected at m/z 165.084 and m/z 167.053, respectively [38,39]. Additional emissions of compounds from the mask associated with this chemical class were silicic acid, trimethylsilyl ester (>1 ppb V ) and 1,1,3,3-tetramethyl-2-oxa-1,3disilacyclohexane (<1 ppb V ), as has been reported previously [6,7].…”
Section: Materials Emissionsmentioning
confidence: 99%
“…A significant fragmentation of toluene could also not be observed, meaning that the humidity and the formation of water clusters did not have an influence on the fragmentation pattern, which otherwise could affect the sensitivity. [29] After switching off the injection of toluene as well as the water injection, a signal drop is observed within less than 50 cycles, showing a low memory effect of toluene and water (Fig. S13).…”
Section: Trace Analysis With Ptr-msmentioning
confidence: 99%
“…However, to validate the herein simulated data with real gas mixtures from steel mill emissions, compounds or moreover gas mixtures also have to be remeasured under humid conditions, since only in this way impurities and reasons for the deactivation of catalysts can be detected in detail. [29,42,43] Before analyzing the obtained data, the signal has to be normalized to the obtained values of the reagent ion. Therefore, the ion signal of RH + is normalized to the primary ion (H 3 O + ) signal of 10 6 counts per second (cps) (Eq.…”
Section: Trace Analysis With Ptr-msmentioning
confidence: 99%
See 1 more Smart Citation